Penerapan Metode Pembelajaran Mind Mapping Untuk Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Fiqih - Habibi, Wildan; Munif R., M. (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
The teacher occupies an important position and determines the success of the achievement of goals in a learning process. Choosing the right learning method is something that needs to be considered by teachers. This method of mind mapping can improve student learning achievement. Based on this, research was conducted with the title application of Mind Mapping Learning Methods to Improve Student Learning Achievement in Fiqh Subjects Class X IIS at MA Sunan Gunung Jati Gurah Kediri Year of Study 2020/2021. The purpose of the research in this thesis is to find out the learning achievement of students of class X IIS fiqh subjects in MA Sunan Gunung Jati Gurah Kediri after the application of Mind Mapping learning methods is given. The research subject was a student of class X IIS MA Sunan Gunung Jati Gurah Kediri as many as 12 students. The data collection procedure is through student learning outcome tests, student activity observation sheets, and the dissemination of student response questionnaires. The approach in this study uses a qualitative approach because with a qualitative approach researchers can decipher the data obtained. The study used class-action research that lasted for two cycles and preceded pre-cycles. Based on the results of cycle 1 and cycle 2 by looking at data from the pre-cycle, data can be obtained that, students who have not completed in pre-cycle reached 41.6% or 5 students from 12 students. While the completed amounted to 58.3% or 7 students. While in cycle I have increased to 25% or 3 students who have not reached completion, and 75% or 9 students have achieved completion. n cycle II the increase is getting higher with 8.3% or 1 student unfinished and 91.6% or 11 students have achieved completion. Seeing an increase in learning outcomes from pre-cycle to cycle 1 to cycle 2 which has increased, then the application of mind mapping methods can improve the learning outcomes of Grade X IIS MA Sunan Gunung Jati lesson year 2020/2021